A typical gallstone ileus: Clinical, radiological and operational findings - Mehmet Sertkaya; Arif Emre; Sami Akbulut; Halit Vicdan; Ahmet Necati Şanlı (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Sertkaya M, Emre A, Akbulut S, Vicdan H, Şanlı AN. A typical gallstone ileus: Clinical, radiological and operational findings. Turk J Gastroenterol 2019; 30(4): 377-80.